Seroprevalence Study of HbsAg positive in Entrant Candidates of Specialist Doctoral Program at Dr. Kariadi Hospital Semarang - Hery Djagat Purnomo; Suyatmi Awizar (The Indonesian Society for Digestive Endoscopy, 2008)
Background: Hepatitis B Virus (HBV) infection is one of main diseases that infects human kind and constitutes a serious health problem in community. As a consequence of their job, health personnel have gained higher risk to HBV infection. Medical personnel (doctors) are determined as one of the high-risk group of the HBV infection through blood transmission.The objective of this study was to determine the prevalence of HBsAg positive in doctors who were entrant candidates of medical specialist program at Dr. Kariadi hospital. Method: The study was conducted retrospectively by reviewing medical record of 1,145 doctors who were entrant candidates of medical specialist program at Dr. Kariadi hospital since April 2000 to October 2004. The HBsAg assay as a marker of HBV infection was analyzed by EIA (Enzyme Immuno Assay) Method. Results: Among the 1,145 doctors examined , the range of age was 29.34 ± 3.04 years, and more than 3-year work period as doctor was 64% (733/1,145), and less than 3-year work period as doctor was 36% (412/1,145). The prevalence of HBsAg positive in population was 3.9% (45/1,145). The seropositive of HBsAg in the group of doctors with more than 3-year work period was significantly higher than the group with less than 3-year work period (5.1% (38/73) vs. 1.6% (7/412) with p 0.05. Conclusion: The prevalence of HBsAg positive in doctors who were entrant candidates of specialist doctoral program at Dr. Kariadi hospital was 3.9%. The prevalence of infection was higher in the group of doctors with more than 3-year work period. Keywords: prevalence, HBsAg, doctor